2016
DOI: 10.1111/1744-1633.12157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silymarin alcoholic extract on surgery‐induced intraperitoneal adhesion in rats

Abstract: Aim: Adhesion formation is the greatest complication in abdominal surgery. Silybum marianum (S. marianum) extract contains phenolic compounds whit antioxidant activities, thus could reduce adhesion formation. The aim of the present study was to examine its effect on intraabdominal adhesion. Patients and Methods: Thirty male Wistar rats were randomly divided into three groups. Groups A and B received 1 per cent and 5 per cent concentrations of the S. marianum extract, and group C (control group) received distil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The extract was concentrated using vacuum distillation until the volume was reduced to 20 mL. The concentrated extract was dried (18). The placebo capsules consisted of dextrose.…”
Section: Extractionmentioning
confidence: 99%
“…The extract was concentrated using vacuum distillation until the volume was reduced to 20 mL. The concentrated extract was dried (18). The placebo capsules consisted of dextrose.…”
Section: Extractionmentioning
confidence: 99%
“…Various methods are used to create the model of peritoneal adhesion in rats, for instance intestinal abrasion, large intestine anastomosis, ischemic buttons, and peritoneal incisions and removing a piece of the peritoneum [ 41 ]. In the current research, we employed the method of the peritoneal wall incision and removing a piece of peritoneum to induce adhesions, which is known to be one of the acceptable methods [ 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Silymarin has anti-inflammatory, antifibrotic, and antioxidant properties [58,59]. Previous studies have shown that 3 ml, 1% or 5% concentration, of the silymarin extract was administered into the abdominal cavity for 14 days, which is effective to prevent PAA [60,61]. It may be attributed to the inhibition of collagen overproduction and accumulation, and complete lysis of fibrin in the experimental adhesion model of rats.…”
Section: Ligustrazinementioning
confidence: 99%